2010
DOI: 10.1557/mrs2010.527
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Engineering Stem Cell Niches

Abstract: Stem cells have received a lot of attention due to great promises in medical treatment, for example, by replacing lost and sick cells and re-constituting cell populations. There are several classes of stem cells, including embryonic, fetal, and adult tissue specific. More recently, the generation of so-called induced pluripotent stem (iPS) cells from differentiated cells has been established. Common criteria for all types of stem cells include their ability to self-renew and to retain their ability to differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…The alternatives of 3D scaffolds for tissue engineering on the market are vast due to its physiological relevance (Pampaloni, Reynaud et al 2007;Dutta and Dutta 2009;Justice, Badr et al 2009). Its microenvironment can alter the cell phenotype by being a stimulus, effecting proliferation, viability and differentiation (Teixeira, Hermanson et al 2010;Wojcik-Stanaszek, Gregor et al 2011) due to changes in stiffness (Teixeira, Ilkhanizadeh et al 2009), mechanotransduction (Vogel 2006;Hoffman, Grashoff et al 2011) or material functionalization (Pashuck and Stevens 2012;Widhe, Johansson et al 2013). In a context dependent manner -cell type, tissue, and organism -we need to custom make cell-material interactions.…”
Section: Biomaterials For Tissue Engineeringmentioning
confidence: 99%
“…The alternatives of 3D scaffolds for tissue engineering on the market are vast due to its physiological relevance (Pampaloni, Reynaud et al 2007;Dutta and Dutta 2009;Justice, Badr et al 2009). Its microenvironment can alter the cell phenotype by being a stimulus, effecting proliferation, viability and differentiation (Teixeira, Hermanson et al 2010;Wojcik-Stanaszek, Gregor et al 2011) due to changes in stiffness (Teixeira, Ilkhanizadeh et al 2009), mechanotransduction (Vogel 2006;Hoffman, Grashoff et al 2011) or material functionalization (Pashuck and Stevens 2012;Widhe, Johansson et al 2013). In a context dependent manner -cell type, tissue, and organism -we need to custom make cell-material interactions.…”
Section: Biomaterials For Tissue Engineeringmentioning
confidence: 99%
“…Yet few efforts have been made to optimize biocompatible materials for such cells to be expanded and used in clinical conditions. We have previously demonstrated that Several reports from recent years, including from our lab, have demonstrated how substrate characteristics such as stiffness and roughness, and incorporation of specific cell binding motifs influence the differentiation of various types of stem cells in a cell context-specific manner [1][2][3][4]. This is particularly important when addressing neural tissue modeling since threedimensional context of cell-cell interactions and cytoarchitecture is prohibited in conventional 2D cultures.…”
Section: Neural Progenitors or Stem Cells (Nscs) Show Great Promise Imentioning
confidence: 94%
“…Over the past years, researchers have generated extensive evidence that biochemical cell-matrix interactions can improve cell survival and function. Many approaches, including chemical modification of the primary structure of spidroin, gene modification with cell-binding motifs, and the change of the material surface topographies, have been adapted to improve cell behaviors (e.g., cell attachment, proliferation, and differentiation) to scaffolds made of spider silk proteins [21][22][23][24]. Chemical coupling techniques rely on certain chemicals that are not always biocompatible with cells, and the efficiency of this nonspecific adhesion on in vitro culture is relatively low for some types of cells [25].…”
Section: Interactions Between Spider Fibroin and Cellsmentioning
confidence: 99%